PENDAMPINGAN DAN PELATIHAN PENGGUNAAN APLIKASI SIDAWAI BAGI KARYAWAN DI DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN BAGIAN SEKRETARIAT - Uyunun Lusiana; Khairul Imtihan; Wire Bagye; Mohamad Taufan Azri Zaen; Mardi Mardi (Jurnal Abdi Insani, 2023)
The development of information technology has made many organizations and agencies use computers and web-based information technology to help work more effectively and efficiently. The Housing and Settlement Area Office of Central Lombok district, utilizes several information technology systems, one of which is an employee data information system (SIDAWAI) which is used to manage employee data, this system provides employee data information and can make it easier to get employee data information quickly. Sidawai this is not fully usable because there is still employee data that has not been inputted. Because there is still a lot of data on sidawai which have not been inputted is one of the motivations to carry out mentoring and training activities. The purpose of this training activity is to improve skills, streamline and optimize usage and input sidawai. There are 3 stages or methods carried out in this training activity namely, Preparation, Training and Evaluation and Reporting. The results of the implementation of mentoring and training activities were successfully carried out with an understanding level of 82.45%, and the implementation of this training activity ran smoothly and received good and positive responses from the participants. And judging from the initial test chart, there are still many who don't understand at 42.7% with the application sidawai, after the mentoring and training activities were carried out, seen from the final test graph there was an increase in participants' understanding of the application sidawai of 89.52%.